(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The purpose of this paper is to examine the spatial distribution of water balance components for Kaduna State. One of the most important outcomes in the water balance equation for any natural area or water body is Evapotranspiration and it is also a crucial component of the hydrologic cycle. In attaining this, monthly data on temperature (T) and rainfall (P) were obtained from NASA (National Aeronautics and Space Administration) twelve remotely sensed stations around Kaduna State for thirty-seven years from 1984 to 2021. Thornthwaite and Mather Water Balance (WB) model was used to estimate WB components i.e., soil moisture (SM), actual evapotranspiration (AET), Water surplus (S) and Runoff (R). Kaduna State was divided into three sub-basins and the result shown peak of R generally occurs during the wet season (i.e., June through November across the three catchment areas) most especially at Kaduna central catchment area in the month of July (1003.85mm). The study further reveals that the bulk of the rains still occur between these months with the peak being reached in July having the peak of rainy season for the three catchment areas with Galma-1378.21mm, Kaduna Central-1443.82mm and Mada- 814.05mm respectively. The area is relatively dry in the months of November–April and has water deficit while Soil moisture recharge takes place from early May to August and mid-May to December is the period of water surplus across the catchment areas. The result of this study provides a reference information on water balance distribution in Kaduna State and utilization for...